Aspergillus-bees: A dynamic symbiotic association - Becchimanzi, Andrea; Nicoletti, Rosario (Frontiers in Microbiology, 2022)
Besides representing one of the most relevant threats of fungal origin to human and animal health, the genus Aspergillus includes opportunistic pathogens which may infect bees (Hymenoptera, Apoidea) in all developmental stages. At least 30 different species of Aspergillus have been isolated from managed and wild bees. Some efficient behavioral responses (e.g. diseased brood removal) exerted by bees negatively affect the chance to diagnose the pathology, and may contribute to the underestimation of aspergillosis importance in beekeeping. On the other hand, bee immune responses may be affected by biotic and abiotic stresses and suffer from the loose co-evolutionary relationships with Aspergillus pathogenic strains. However, if not pathogenic, these hive mycobiota components can prove to be beneficial to bees, by affecting the interaction with other pathogens and parasites and by detoxifying xenobiotics. The pathogenic aptitude of Aspergillus spp. likely derives from the combined action of toxins and hydrolytic enzymes, whose effects on bees have been largely overlooked until recently. Variation in the production of these virulence factors has been observed among strains, even belonging to the same species. Toxigenic and non-toxigenic strains/species may co-exist in a homeostatic equilibrium which is susceptible to be perturbed by several external factors, leading to mutualistic/antagonistic switch in the relationships between Aspergillus and bees.